An Analytical Study on Usage of E -Resources in Sri Ramachandra Medical College Students in Chennai - Santhanalakshmi, R.; Veerachamy, M. (International Journal of Psychosocial Rehabilitation, 2019)
In recent years an increasing impact of Information and Communication Technology on education all those concerned with higher education today are attempting to grasp how ICT could help in modernizing the process of teaching, learning and doing research. The present article explores an analytical study on usage of e - resources in Sri Ramachandra Medical College students in Chennai. The fifty numbers of questionnaires were distributed and forty one questionnaires are responded in the survey. The study focus the Gender, Age, PubMed Awareness, Purpose of using electronic resources, Place of Access, How Many Hours do you spend in Electronic resources. The majority of the students are using electronic resources are male (82.92%), PubMed awareness (90.24%), Subject learning (24.39%), Place of access an electronic resources in the library (46.36%)